Disentangling Bare Nouns and Nominals Introduced by a Partitive Article - Ihsane, Tabea (Syntax and Semantics, 2020)
This volume edited by Tabea Ihsane focuses on different aspects of the distribution, semantics, and internal structure of nominal constituents with a "partitive article" in its indefinite interpretation and of potentially corresponding bare nouns. It further deals with diachronic issues, such as grammaticalization and evolution in the use of "partitive articles". The outcome is a snapshot of current research into "partitive articles" and the way they relate to bare nouns, in a cross-linguistic perspective and on new data: the research covers noteworthy data (fieldwork data and corpora) from Standard languages - like French and Italian, but also German - to dialectal and regional varieties, including endangered ones like Francoprovençal. Readership: All interested in the syntax-semantics interface of noun phrases with a "partitive article" and their corresponding bare nouns, as well as in diachronic issues, both in Romance and Germanic languages/dialects/varieties.